1996
DOI: 10.1021/jp9608887
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Studies of Ultrathin Films of Linear and Branched Alkanes on a Metal Substrate

Abstract: Ultrathin liquid films of three hexadecane isomers and of squalane physisorbed on a flat metal (Au(111)) surface have been studied by Monte Carlo and molecular dynamics simulations. Density oscillations arising from the layering of methyl and methylene groups on the surface are observed in all films. Branched molecules exhibit a decreased tendency to layer and an enhancement in the degree of interdigitation. Comparisons are made with recent surface force experiments and other simulation studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…in what extent individual molecules go from one layer to another, increases in the case of branched alkanes. This effect is already shown in [35], where molecules with many side branches (like squalane) reveal a large amount of interdigitation near a single wall. These bridges between the individual layers may be a reason for this longrange attractive force.…”
Section: Resultssupporting
confidence: 54%
“…in what extent individual molecules go from one layer to another, increases in the case of branched alkanes. This effect is already shown in [35], where molecules with many side branches (like squalane) reveal a large amount of interdigitation near a single wall. These bridges between the individual layers may be a reason for this longrange attractive force.…”
Section: Resultssupporting
confidence: 54%
“…Molecular dynamics simulations have shown that layering occurs due to the confinement of molecules near solid-liquid interfaces [8][9][10]27,28]. For squalane, simulations show the alkane chains to be oriented parallel to the interface with a 4 -5 Å spacing between the molecular layers [27,28]. We will attribute the 8 Å steps to correspond to bilayers that may form when molecules interdigit between layers or coil back on themselves.…”
Section: Shear Response Of Molecularly Thin Liquid Films To An Appliementioning
confidence: 92%
“…The presence of steps in spreading films is frequently cited as evidence for liquid molecules layering at the solid-liquid interface [24][25][26]. Molecular dynamics simulations have shown that layering occurs due to the confinement of molecules near solid-liquid interfaces [8][9][10]27,28]. For squalane, simulations show the alkane chains to be oriented parallel to the interface with a 4 -5 Å spacing between the molecular layers [27,28].…”
Section: Shear Response Of Molecularly Thin Liquid Films To An Appliementioning
confidence: 99%
“…The oscillatory solvation force is associated with density oscillations [8,13], which are in turn dependent on the de-gree of layering and intralayer ordering of liquid molecules at the liquid-solid interface [8][9][10][11][12]. The simulations reveal that layering should occur in heavily branched alkanes (e.g., squalane and 2-, 6-, 11-, 15-tetramethylhexadecane), although to a lesser degree in comparison with linear chain alkanes, such as n-hexadecane [9,11,12]. Additionally, density layering effects have been observed by molecular dynamics for freestanding branched decane isomer films at the liquid-solid interface [14].…”
mentioning
confidence: 99%